Healthy Gut, Healthy Bones: Targeting the Gut Microbiome to Promote Bone Health - Cooney, Olivia D.; Nagareddy, Prabhakar R.; Murphy, Andrew J.; Lee, Man K. S. (Frontiers in Endocrinology, 2021)
Over the past decade, the use of probiotics to modify the gut microbiome has become a public spotlight in reducing the severity of a number of chronic diseases such as autoimmune disease, diabetes, cancer and cardiovascular disease. Recently, the gut microbiome has been shown to play an important role in regulating bone mass. Therefore, targeting the gut microbiome may be a potential alternative avenue for those with osteopenia or osteoporosis. In this mini-review, we take the opportunity to delve into how the different components of the gut work together and how the gut-related diseases impact on bone health.